Photogrammetry based space analysis measurements in orthodontic diagnosis - Arapović-Savić Marijana; Savić Mihajlo; Umićević-Davidović Mirjana; Arbutina Adriana; Nedeljković Nenad; Glišić Branislav (Serbian Medical Society - Dental Section, Belgrade, 2018)
Introduction Lundstrom segmental analysis is often used analysis in orthodontic diagnosis. It includes measurements of available and needed space in the arch in order to determine whether there is a lack or excess of space for proper teeth alignment. Measurements are traditionally performed on plaster study models, but with recent developments of computer-based systems, there is an increase in use of digital models in measuring process. The aim of this study was to present a photogrammetry based measurement approach that requires no specialized and expensive hardware and compare results with ones obtained on 3D scanned models. Material and method On 50 plaster study models measurements of 24 teeth, widths of 12 segments and Lundstrom segmental analysis were performed. 3D scanned study models were analyzed in the photogrammetry software OrthoPhoto4D on the set of four photographs of the study model in custom made measurement apparatus. The software corrects for finite distance of the camera and corrects errors due to perspective distortion. Results Statistical analysis performed on obtained measurements provided Bland-Altman plots that strongly suggested high degree of correspondence between the two measurements methods. Discrepancies for maxilla for individual segments were under 0.25 mm with standard deviation of up to 0.16 mm, and less than 1 mm and deviation of up to 0.4 mm for complete arch. For mandible the differences were up to 0.27 mm for segments with 0.15 mm deviation and 0.6 mm for complete arch with up to 0.24 mm deviation. Correlation coefficient was over 0.985 in all cases. Conclusions Both analyzed methods can be equally used in clinical practice.